Lipid‐based strategies used to identify extracellular vesicles in flow cytometry can be confounded by lipoproteins: Evaluations of annexin V, lactadherin, and detergent lysis. Issue 4 (31st March 2022) - Botha, Jaco; Handberg, Aase; Simonsen, Jens B.
Abstract: Flow cytometry (FCM) is a popular method used in characterisation of extracellular vesicles (EVs). Circulating EVs are often identified by FCM by exploiting the lipid nature of EVs by staining with Annexin V (Anx5) or lactadherin against the membrane phospholipid phosphatidylserine (PS) and evaluating the specificity of the labels by detergent lysis of EVs. Here, we investigate whether PS labelling and detergent lysis approaches are confounded by lipoproteins, another family of lipid‐based nanoparticles found in blood, in both frozen and fresh blood plasma. We demonstrated that Anx5 and lactadherin in addition to EVs stained ApoB‐containing lipoproteins, identified by the use of fluorophore‐labelled polyclonal ApoB‐antibody, and that Anx5 had a significantly larger tendency for labelling lipoprotein‐bound PS than lactadherin. Furthermore, detergent lysis resulted in a decrease in both EV and lipoprotein events and especially lipoproteins positive for either Anx5 or lactadherin. Taken together, our findings pose concerns to the use of lipid‐based strategies in identifying EVs by FCM and support the use of transmembrane proteins such as tetraspannins to distinguish EVs from lipoproteins.